Pathogenicity of banana blood disease bacterium HR2 Mardi and characterization of its virulent proteins - Bakar, Ros Azrinawati Hana (2018)
In Malaysia, bacterial wilt has been identified as one of the main constraints for banana production. Blood Disease Bacterium (BDB) is a gram negative bacteria that caused Banana Blood Disease (BBD) which identified as one of the most important pathogen of banana (Musa sp.) which could infect almost all cultivated banana varieties. On the other hand, BDB is grouped into Phylotype IV which placed in a subgroup of the R. solanacearum species complex. BDB was reported to be pathogenic to a single host, banana. Hence, the first objectives of this study is to determine the host range and symptomatology study of BDB on selected hosts. Results from this study showed that BDB only pathogenic to banana not to other tested hosts such as tomato (Solanum lycopersicum) and heliconia (Heliconia sp.) and confirmed to be virulence and able to infect banana. The disease symptoms were wilting of leaves, discoloration of vascular tissues and eventually leads to plant death. The second objectives of this study is to identify and quantify effector protein(s) of BDB in selected media. From this study, findings indicated that 17 potential virulent proteins were obtained from virulence inducing media (M63). Prediction of virulence characteristics shows that the only five proteins were found to be effector proteins of BDB. The proteins were Signal peptidase, Lipoprotein, Uncharacterized protein, Membrane protein and Serine protease. In conclusion, BDB was confirmed to be a single host-pathogen to banana (Musa sp.) plant, and confirmed to be virulence for the proteomics study and based on proteomics analysis revealed five virulent proteins, namely Signal peptidase, Lipoprotein, Uncharacterized protein, Membrane protein and Serine protease associated with the virulence of BDB.